Repurposing agricultural waste as low-cost cultured meat scaffolds - Perreault, Luke R.; Thyden, Richard; Kloster, Jack; Jones, Jordan D.; Nunes, Jordan; Patmanidis, Andriana A.; Reddig, David; Dominko, Tanja; Gaudette, Glenn R. (Frontiers in Food Science and Technology, 2023)
Growing meat in vitro using tissue engineering and bioproduction techniques (cellular agriculture) has become an increasingly promising solution to the global food security challenge. Our lab has established methods to cultivate bovine muscle tissue on decellularized plants, representing a viable low-cost, sustainable method to grow meat on edible scaffolds. Most work in this area has focused on the use of edible plant materials (i.e., spinach leaves, apple, broccoli) with inherent economic value. Harvest waste such as corn husk or jackfruit represent abundant sources of cellulose for scaffold production and may be a viable alternative. The present study aims to investigate production of cultured meat through tissue engineering and bioproduction on decellularized, edible samples of corn husk and jackfruit rind. Corn husks and jackfruit rinds were exposed to immersion decellularization. DNA quantification and histological analysis demonstrated sufficient decellularization (0.17 ± 0.06 and 0.07 ± 0.00 ug DNA/g tissue for corn husk and jackfruit rinds, respectively). Following decellularization, corn husk scaffold stiffnesses decreased from 56.67±16.71 MPa to 12.95±2.43 MPa in fiber-aligned direction, while jackfruit decreased from 7.54 ±2.42 MPa to 2.47±1.47 MPa. Seeded scaffolds with bovine satellite cells (BSCs) (11.45±2.24 ug/ul lysate/Gram) and avian (QM7s) (12.90±1.99 ug/ul lysate/Gram) demonstrated increased protein yields on jackfruit scaffolds. QM7 cultured on corn husk scaffolds yielded increased protein but PBSCs seeded on corn husks did not yield protein content higher than controls (QM7 on corn husk: 16.28±3.55, PBSCs on corn husks: 9.57±1.56 ug/ul lysate/Gram, control: 6.35±1.43 ug/ul lysate/Gram). Additionally, cell transfer from scaffold to scaffold (bead-to-bead transfer) was observed on corn husk scaffolds in a dynamic environment. These results suggest that decellularized harvest waste scaffolds may aid in realization of cultured meat products that will contribute to a more robust and environmentally sustainable food supply.